2007
DOI: 10.1016/j.ijgo.2007.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic entry techniques and complications

Abstract: This survey demonstrates the variation in entry techniques used by gynecologists in the United Kingdom. Without a good evidence-base to the contrary no entry technique can be stated as safer than another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
1
17
0
1
Order By: Relevance
“…Direct entry was used by 1.1% of respondents, with no mention of DOA. 7 As a result of these considerations on abdominal laparoscopic access, the findings of this preliminary study suggest that the DOA technique might represent in postmenopausal women not undergoing HT a safe and less time-consuming approach to abdominal entry, avoiding the risks of blind access laparoscopy. However, these data are still preliminary in terms of clinical morbidity, and to date there are no sufficient randomized studies on the safety of DOA.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Direct entry was used by 1.1% of respondents, with no mention of DOA. 7 As a result of these considerations on abdominal laparoscopic access, the findings of this preliminary study suggest that the DOA technique might represent in postmenopausal women not undergoing HT a safe and less time-consuming approach to abdominal entry, avoiding the risks of blind access laparoscopy. However, these data are still preliminary in terms of clinical morbidity, and to date there are no sufficient randomized studies on the safety of DOA.…”
Section: Discussionmentioning
confidence: 77%
“…Conversely, there are studies on other entry methods, such as open laparoscopy, described by Hasson,21 or the closed-entry technique by direct access, 22 or the Veress needle. 4/6,23 In fact, a recent study by Ahmad et al, 7 based on the prevalence of first-entry methods in laparoscopy, evaluating the practice of gynecologists in the United Kingdom revealed that the closed Veress needle entry technique was used by 93.8% of respondents; alternative methods including the open technique were only used by 5.2% of surgeons. Direct entry was used by 1.1% of respondents, with no mention of DOA.…”
Section: Discussionmentioning
confidence: 99%
“…Our national questionnaire study showed considerable heterogeneity in laparoscopic entry practice despite widespread awareness of the Middlesbrough Consensus or RCOG-sourced guidance. The inconsistency, inherent throughout every step of the laparoscopic entry procedure, has been identified by previous UK-based surveys [90][91][92][93]. Fundamentally, there was a failure to appreciate risk factors that would justify a change in entry technique as well as failure to adopt the correct safety checks after Veress insertion and before primary trocar insertion.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant variation in laparoscopic entry practice in the United Kingdom [90][91][92][93] and at international locations [27,94,95]. In an attempt to minimize the risks of laparoscopy and unify clinical practice, a number of international bodies (International Middlesbrough Consensus [96], RCOG [draft version only] [97], SOGC [78], RANZ-COG [98], EAES [99], Society of American Gastrointestinal Endoscopic Surgeons [SAGES] [100], the French Society of Endoscopic Gynecology [101], the Netherlands [102] and individual experts [103][104][105]) have recommended specific ''safe laparoscopic entry'' principles.…”
mentioning
confidence: 99%
“…Vessels located beneath the umbilicus were analyzed. Despite its many benefits, especially during entry, laparoscopic surgery is associated with serious complications such as gastrointestinal tract and vascular injuries (Liu et al, 2009;Ahmad et al, 2007;Krishnakumar & Tambe, 2009). Vascular injury is a major cause of death from laparoscopic surgery, with a reported mortality rate of 15% (Krishnakumar & Tambe).…”
Section: Introductionmentioning
confidence: 99%